Why Don't Jobseekers Search More? Barriers and Returns to Search on a Job Matching Platform - Kate Vyborny; Robert Garlick; Nivedhitha Subramanian; Erica Field (Institute of Labor Economics (IZA), 2024)
Understanding specific barriers to job search and returns to relaxing these barriers is important for economists and policymakers. An experiment that changes the default process for initiating job applications increases applications by 600% on a search platform in Pakistan. Perhaps surprisingly, the marginal treatment-induced applications have approximately constant rather than decreasing returns. These results are consistent with a directed search model in which some jobseekers miss some high-return vacancies due to psychological costs of initiating applications. These findings show that small reductions in search costs can substantially improve search outcomes in environments with some relatively inactive jobseekers.
Keywords: J20; J60; O10; 330; behavioural economics; job search; search frictions; platform